Implementation of local tax audits and local tax collection at the Regional Revenue Agency of Bengkulu City - Dian Anggraini; Andri Marfiana (Educoretax, 2026)
This study analyzes the implementation of local tax audits and local tax collection at the Regional Revenue Agency of Bengkulu City, their conformity with national regulations, and the factors influencing their implementation. This study employed a qualitative case study approach. Data were collected through semi-structured interviews, observation, and document analysis, and were analyzed using the interactive model of Miles et al. with Edwards III’s policy implementation theory as the analytical framework. The findings show that local tax audits and collection have been implemented but have not optimally supported the examination of taxpayer compliance and the settlement of tax obligations. Audits remain focused on administrative verification, particularly field verification in handling objections to Land and Building Tax – Urban and Rural, rather than serving as a comprehensive compliance-examining instrument. Tax collection is still dominated by administrative and persuasive measures, while active collection has not been implemented optimally. Although implementation is formally supported by local regulations, mayoral regulations, and standard operating procedures, the technical instruments have not been fully aligned with the latest national regulatory framework. The implementation is influenced by ineffective policy communication, limited resources, implementer disposition and taxpayer response, and a bureaucratic structure that has not fully supported technical implementation. Keywords: local tax audit, local tax collection, policy implementation, local tax, Regional Revenue Agency of Bengkulu City.